Reconstruction using a free vascularised medial femoral condyle corticoperiosteal flap for osteomyelitis of the juxta-articular distal radius: A case report and literature review. (April 2021) - Suganuma, Seigo; Tada, Kaoru; Yamauchi, Daisuke; Takagawa, Shingo; Yasutake, Hidetoshi; Shimanuki, Keito; Tsuchiya, Hiroyuki
Abstract: Osteomyelitis of the epiphysis after a distal radius fracture is uncommon. If not adequately and promptly treated, the detrimental effects on wrist function can be devastating. However, management of septic bone defects of the epiphysis is significantly challenging. We report the case of a patient with juxta-articular distal radius osteomyelitis successfully treated with a free vascularised corticoperiosteal flap from the medial femoral condyle (MFC corticoperiosteal flap). A 46-year-old right-handed man fell on the grass from a height of 2 m during a demolition. He was diagnosed with a right distal radius and ulnar styloid process fracture. He underwent open reduction and internal fixation. However, he developed a deep infection, resulting in postoperative osteomyelitis. Therefore, thorough debridement was performed and an external fixator was applied. Antibiotics were administered according to the culture results. He underwent reconstruction for bone defect using an MFC corticoperiosteal flap 28 days after re-operation. The patient could resume work without limitations 4 months after the reconstruction. The infection subsided completely, and radiographs confirmed bone union at 5 months after the reconstruction. His wrist range of motion was 40° in dorsal flexion (uninjured side 70°), 50° in palmar flexion (75°), 80° in supination (90°), and 90° in pronation (90°). There was no donor site complication. The patient has reported no pain for 1 year since the injury. The use of the MFC corticoperiosteal flap for reconstruction of the juxta-articular distal radius osteomyelitis decreased the time required for bone union, enabled local antibiotic delivery to control infection, and helped preserve wrist function.